2010
DOI: 10.3144/expresspolymlett.2010.50
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of nano-silica in monomer casting nylon6 and its effect on the structure and properties of composites

Abstract: Abstract.To promote dispersion of nano-silica in monomer casting nylon6 (MC nylon6), nano-silica was dispersed in melted caprolactam with the assistance of ultrasound, anionic polymerization was then initiated to form silica/MC nylon6 in-situ nanocomposites. It was found that hydrogen bonds were formed between nano-silica and caprolactam, in the meantime, ultrasound helped to break the nanoparticles aggregations into smaller ones or even mono-dispersing particles. Therefore, the agglomerated nanoparticles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…According to Theng 32 and Velde 33 , the interaction between the amide groups of PA6 molecules and the ionic groups at the clay surfaces probably suppresses thermal degradation of the composite matrix. However, it is interesting to find that thermal stability of nanocomposites is slightly inferior to the virgin PA6 when higher weight loss (90%) is considered, the same results are obtained by Cai et al,34 . Such results indicate that the introduction of clay might change the decomposition mechanism of PA6 under high temperature.…”
Section: Thermogravimetry (Tg)supporting
confidence: 70%
“…According to Theng 32 and Velde 33 , the interaction between the amide groups of PA6 molecules and the ionic groups at the clay surfaces probably suppresses thermal degradation of the composite matrix. However, it is interesting to find that thermal stability of nanocomposites is slightly inferior to the virgin PA6 when higher weight loss (90%) is considered, the same results are obtained by Cai et al,34 . Such results indicate that the introduction of clay might change the decomposition mechanism of PA6 under high temperature.…”
Section: Thermogravimetry (Tg)supporting
confidence: 70%
“…The results showed that the impact strength, tensile strength, and modulus of composites were doubled compared to pure MC nylon, while the thermal performance was also improved with 2 wt% of silica. He et al [4] prepared Y(OH) 3 /MC nylon composite, and it was found that with the incorporation of 0.25 wt% of Y(OH) 3 , the toughness of the composite increased by 60 %, and the water absorption reduced by 34 %, but the thermal stability barely changed. Huang et al [5] used the hydrotalcite as filler to prepare MC nylon composites.…”
Section: Introductionmentioning
confidence: 96%
“…It has been reported on utilizing nanomaterial to toughen MC nylon in various papers. Cai et al [3] added nanosilica into the melting caprolactam to prepare MC nylon nanocomposites by in situ polymerization. The results showed that the impact strength, tensile strength, and modulus of composites were doubled compared to pure MC nylon, while the thermal performance was also improved with 2 wt% of silica.…”
Section: Introductionmentioning
confidence: 99%
“…by sol-gel processing 22 or the in situ polymerization of ε-caprolactam in presence of preformed silica particles. 15,[23][24][25][26] The grafting of PA6 on surface functionalized SiO 2 particles is also a suitable route to fabricate polymer/SiO 2 hybrid materials. 27,28 As an additional way, the simultaneous formation of both polymer components within one procedure is known.…”
Section: Introductionmentioning
confidence: 99%